33 Estimating unnecessary lumbar imaging rates in NSW emergency departments (ED). (4th December 2019) - Traeger, Adrian; Tcharkhedian, Elise; Coombs, Danielle; Oliveira, Crystian
Abstract : Objectives: In 2018 clinicians provided diagnostic imaging tests to almost half of all patients who present to a NSW ED with low back pain. It is unclear how many of these tests were unnecessary. We aimed to determine whether a system to estimate unnecessary imaging rates could be developed and validated in NSW Hospital EDs. Method: Two clinician researchers will screen the clinical charts of people who presented to a NSW ED for low back pain over a one month period. The researchers will read the clinical notes, reason for imaging request, ED discharge letter, ED imaging report, and hospital admission report to judge appropriateness. Using a checklist of guideline indications for urgent imaging, researchers will code each imaging order as being 'appropriate, ' 'potentially appropriate' 'unnecessary, ' or 'unable to determine appropriateness.' To determine reliability of the coding system we will calculate agreement (Kappa).To detect a kappa >=0.6 with 90% power, two raters will review a minimum 255 clinical charts each. This estimate assumes a two-tailed test with a null value of kappa=0.4, proportion of positive ratings =0.3 (ie we expect ∼30% lumbar imaging tests will be rated as 'appropriate'). Results: Results will be presented at the conference. Conclusions: This study will be the first to estimate the rate of unnecessary diagnostic imaging for low back pain in NSW EDs based on comprehensive case note reviews.